Sovereigns going bust: estimating the cost of default - Dmitry Kuvshinov; Kaspar Zimmermann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2016)
This paper estimates the cost of sovereign default by using novel econometric methods – dynamic local projections applied to a sample that is re-randomised using inverse propensity score weights. We find that the impact of default on output is negative, significant and persistent – around 2.8% of GDP on impact and 4.8% at peak. The downturn is driven by sharp falls in investment, accompanied by a collapse in gross trade. The cost rises dramatically if the default is followed by a systemic banking crisis, peaking at 9.5% GDP. Our findings suggest that while autarky costs play an important role, sovereign-banking spillovers are central to the cost of default.
Keywords: H63; F34; 330; Sovereign default; sovereign debt; banking crises; treatment effects; local projections; inverse propensity score weighting